Historiography of Pre-Islamic Arab In The East and West - Haringun Trisiwi Adhi Rachmawati (Green Publisher Indonesia, 2025)
This study analyzes the various problems that arise in writing the history of the pre-Islamic period, especially related to the limitations of historical sources, interpretation, and bias in traditional historiography. The method used in this research is a literature review, utilizing a comparative approach between the results of modern historiography and the findings of recent research. The research shows that the development of modern social sciences, such as archaeology, anthropology and linguistic studies, made a significant contribution in overcoming these challenges. With a multidisciplinary approach, modern historiography is able to provide a more comprehensive and accurate picture of the pre-Islamic period, while minimizing the interpretative biases that have limited understanding of the period. The results of this study support the importance of integrating modern social sciences in rewriting history to produce a more objective and comprehensive narrative.